A scoping review on self-regulation and reward processing measured with gambling tasks: Evidence from the general youth population. - Francesca Bentivegna; Efstathios Papachristou; Eirini Flouri (PLoS ONE)
Aberrant reward processing and poor self-regulation have a crucial role in the development of several adverse outcomes in youth, including mental health disorders and risky behaviours. This scoping review aims to map and summarise the evidence for links between aspects and measures of reward processing and self-regulation among children and adolescents in the general population. Specifically, it examined the direct associations between self-regulation (emotional or cognitive regulation) and reward processing. Studies were included if participants were <18 years and representative of the general population. Quantitative measures were used for self-regulation, and gambling tasks were used for reward processing. Of the eighteen studies included only two were longitudinal. Overall, the direction of the significant relationships identified depended on the gambling task used and the self-regulation aspect explored. Emotional regulation was measured with self-report questionnaires only, and was the aspect with the most significant associations. Conversely, cognitive regulation was mainly assessed with cognitive assessments, and most associations with reward processing were non-significant, particularly when the cognitive regulation aspects included planning and organisational skills. Nonetheless, there was some evidence of associations with attention, cognitive control, and overall executive functioning. More longitudinal research is needed to draw accurate conclusions on the direction of the association between self-regulation and reward processing.